Characters of real special 2-groups - Kaur, Dilpreet; Kulshrestha, Amit (Ramanujan Mathematical Society, 2015)
It is well-known that special 2-groups can be described in terms of quadratic maps over fields of characteristic 2. In this article we develop methods to compute conjugacy classes, complex representations and characters of a real special 2-group using quadratic maps alone. © 2015 Ramanujan Mathematical Society.
Keywords: special 2-groups; quadratic maps; compute conjugacy classes